(untitled) - Osama Jassim Mohsen Al Safi; Ali Shukr Daoud Al-Hayali (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
Praise be to God who sent down the Book to His servant and did not make him crooked, and blessings and peace be upon the one who was sent as a mercy to the worlds, God sent him with guidance and the religion of truth to be a warner to the worlds, and upon his pure and pure family from whom he removed impurity and purified them with a thorough purification, and upon his faithful companions of the Emigrants and Ansar, who followed him in an hour hardship and reward them with a conquest soon.